2015
DOI: 10.1097/sla.0000000000001391
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Positive Circumferential Resection Margins Following Rectal Cancer Surgery

Abstract: Objective To identify predictors of positive circumferential resection margin following rectal cancer resection in the United States. Background Positive circumferential resection margin is associated with a high rate of local recurrence and poor morbidity and mortality for rectal cancer patients. Prior study has shown poor compliance with national rectal cancer guidelines, but whether this finding is reflected in patient outcomes has yet to be shown. Methods Patients who underwent resection for stage I-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 29 publications
6
86
3
1
Order By: Relevance
“…Our series also demonstrates the aggressive pathological phenotypes of rectal cancers with positive CRM encountered in our population. Factors associated with positive CRM including APR as mode of surgery, worsening tumour grade, increased T‐stage, vascular and perineural invasion have previously been established . Patients undergoing APR are more likely to have locally advanced and distal tumours increasing the complexity of resection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our series also demonstrates the aggressive pathological phenotypes of rectal cancers with positive CRM encountered in our population. Factors associated with positive CRM including APR as mode of surgery, worsening tumour grade, increased T‐stage, vascular and perineural invasion have previously been established . Patients undergoing APR are more likely to have locally advanced and distal tumours increasing the complexity of resection .…”
Section: Discussionmentioning
confidence: 99%
“…Despite pre‐operative local staging with magnetic resonance imaging (MRI), the widespread uptake of the total mesorectal excision technique and use of neoadjuvant radiation patients continue to remain at risk of positive CRM. Examples in recent studies range from 7.8% to 21% in centres located in Australia, New Zealand, USA, UK and Canada . Several factors have been associated with CRM status including technical performance, social demographics, hospital case load, neoadjuvant therapies, procedure performed (low anterior resection versus abdominoperineal resection (APR)) and tumour biology .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was limited to cases of adenocarcinoma, mucinous adenocarcinoma and signet ring cell carcinoma on histology as these accounted for the largest proportion. Mucinous adenocarcinoma and signet ring cell carcinoma were considered separately due to the association of these histologies with more aggressive disease than typical adenocarcinoma as was done in previous NCDB studies 16 17. The sample was further limited to those who had undergone a documented proctectomy.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of CRM (6.8%) and R1 (6.9%) resections were consistent with current literature for NOB patients. Large national studies have shown CRM rates as low as 7.7% to higher rates of 21.1% . The lower rate seen in OB patients can be due to a number of factors, such as tumour size, type of operation, the degree of lymphovascular and perineural invasion, as shown in the Consortium for Optimizing the Treatment of Rectal Cancer (OSTRiCh) study .…”
Section: Discussionmentioning
confidence: 99%